A Study of Sexual Dysfunction Among Psychiatric Patients Receiving Psychotropic Medication - Gyanendra Kumar; Dinesh Singh Rathor; Sandhyarani Mohanty (Journal of Psychosexual Health)
Background: Sexual dysfunction is common in patients with psychiatric disorders and also considered as a known adverse effect of psychotropic medications. Aim: This study aimed at delineating the sociodemographic and clinical correlates of various types of sexual dysfunction among psychiatric patients receiving psychotropic medications. Materials and Methods: It was a cross-sectional hospital-based study conducted at Institute of Mental health and hospital, Agra. The sample consisted of 210 married psychiatric patients of both the genders between the age range of 20–59 years who were on regular treatment with psychotropic medications for at least three months at the outpatient department (OPD) of the institute. The patients having sexual dysfunction before the start of psychotropic medications were excluded from the study. The International Index of Erectile Function (IIEF) and the Female Sexual Function Index (FSFI) were used. Results: Age, duration of illness, duration of treatment, and occupation were significantly associated with erectile dysfunction, intercourse dissatisfaction, orgasmic dysfunction, sexual desire dysfunction, and overall dissatisfaction in male patients but medicine compliance was associated with sexual desire dysfunction only. Education, domicile, and socioeconomic status were not associated with any of the sexual dysfunction domains in male patients. Age, duration of illness, and duration of treatment occupation were significantly associated with desire, arousal, lubrication, orgasm satisfaction, and pain in female patients. Medicine compliance was also associated with each dysfunction except arousal dysfunction. Education, domicile, and socioeconomic status were not associated with any of the sexual dysfunction domains in female patients. Conclusion: The results of this study clearly suggest that the demographic variables of age, occupation and clinical variables of duration of illness, and duration of treatment are significantly associated with sexual dysfunction in both male and female patients. Medicine compliance is a significant factor in female sexual dysfunction more than that is seen in male patients. Both clinical and nonclinical variables contribute to the sexual dysfunction in the psychiatric patients.